APLIKASI PENGELOLAAN HAMA TERPADU KUMBANG TANDUK (ORYCTES RHINOCEROS L.) DI NAGARI GIRI MAJU KABUPATEN PASAMAN BARAT - Efendi, Siska (Jurnal Hilirisasi IPTEKS, 2021)
The oil palm cultivated in the replanting area does not grow optimally because it was mostly attacked by rhinoceros beetle (Oryctes rhinoceros L.). The percentage of hornet beetle attacks is relatively high, at 80% in plants aged three years and 100% at 1-1.5 years. It was known that the residual waste replanting is the cause of the high population of horn beetles because the decayed palm oil stems become a suitable habitat for the development of these pests. To overcome the problems faced by partners, Integrated Pest Management (IPM) was applied. IPM components to be applied are cultural control, mechanical, and semiochemical control with pheromones. Community service was carried out using counseling methods, training, demonstration plots, providing equipment and machinery, as well as monitoring and evaluation. IPM technology assemblies that have been applied can reduce the attack rate of rhinoceros beetle from 86.68% to 79.60%. Until now, IPM equipment is still installed and operated by partner farmer groups. At the end of the activity, the partner farmer groups can apply IPM independently in their respective fields. Sustainable IPM applications, covering large-scale land, involving all palm oil business actors will increase the success of the method in the future.